Comparative Biochemical and Functional Studies on a Branded Human Recombinant Factor VIIa and a Biosimilar Equivalent Product. (September 2014) - Sadeghi, Nasiredin; Kahn, Daniel; Syed, Daneyal; Iqbal, Omer; Abro, Schuharazad; Eshraghi, Reza; Hoppensteadt, Debra; Fareed, Jawed
Recombinant factor VIIa (rFVIIa; NovoSeven, Novo Nordisk, Copenhagen, Denmark) is used to control bleeding in patients with hemophilia. A generic version of FVIIa was developed by AryoGen (Tehran, Iran). This study compared the composition and functional activities of AryoSeven and NovoSeven. Each product was compared at equigravimetric (1 mg/mL) stock solution for protein content. The proteomic profile was obtained using surface-enhanced laser desorption ionization mass spectrometry. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis was carried out to determine the protein profile and Western blotting was performed using a polyclonal rabbit antihuman FVIIa antibody. The FVIIa-related antigen was also measured using a commercially available enzyme-linked immunosorbent assay method. Functional assay included the prothrombin time correction in FVII-deficient plasma. The protein content was comparable in 2 products and the mass spectra analysis showed a single peak at 50 kDa in all products. The SDS-PAGE and immunoblotting studies were comparable. Both products exhibited similar coagulant properties in different assays.